The Holy Grail of Tissue Engineering? Islet Cell Microencapsulation in Type 1 Diabetes Mellitus - Woods, Brian (Trinity Student Medical Journal, 2015)
The immunoisolation of transplanted islet cells represents a promising future therapy for the treatment of type 1 diabetes mellitus (T1DM). Microencapsulation is one avenue being explored to restore insulin independence while simultaneously protecting islet cells from destruction by the immune system. A variety of techniques have been developed to encapsulate the islet cells, with alginate being the most commonly employed biomaterial. The great challenge in microencapsulation is to ensure that the capsule is permselective, allowing for the free diffusion of oxygen, nutrients and waste products while providing an effective barrier to cytokines and immune identification. Other alternatives including nanoencapsulation and conformal coating are emerging. In vivo work is now beginning to be translated into clinical trials.